Fikih Difabel: Analisis Hukum Menceraikan Pasangan yang Menjadi Difabel - Billah, Mu'tashim (PLD UIN Sunan Kalijaga, 2024)
Studies on the rights of persons with disabilities in the private sphere need attention. This is because several regulations legitimize discrimination against persons with disabilities. In a divorce, for example, a normal couple can divorce their partner on the grounds of disability, which they fear will interfere with their rights and obligations in the household. This article examines the law on divorcing couples who become disabled holistically, from laws, regulations, and fiqh. This article is normative research by examining laws from the perspective of norms. This article is literature research by examining sources from the available texts. This article uses an ushul fiqh approach that emphasizes the reinterpretation of story verses as a basis for ijtihad. This article finds that divorce should not be based solely on the cause of the spouse is disabled. This means that divorce must be based on a more substantive element: a broken marriage. Broken marriages are not always born from the cause of a partner who becomes disabled. Many cases show that even though the couple is still normal, they are ignorant of their obligations in the household. Kajian mengenai hak-hak difabel dalam ranah privat perlu mendapat perhatian lebih. Pasalnya, beberapa peraturan justru melegitimasi diskriminasi atas difabel. Dalam perceraian misalnya, pasangan yang normal dapat menceraikan pasangannya dengan alasan difabel yang dikhawatirkan akan mengganggu hak dan kewajibannya dalam rumah tangga. Artikel ini mengkaji hukum menceraikan pasangan yang menjadi difabel secara holistik, baik dari peraturan perundang-undangan dan fikih. Artikel ini merupakan penelitian normatif dengan mengkaji hukum-hukum dari perspektif norma. Artikel ini merupakan penelitian pustaka dengan mengkaji sumber-sumber literatur yang berasal dari teks-teks yang tersedia. Artikel ini menggunakan pendekatan ushul fikih yang menekankan pada reinterpretasi ayat-ayat kisah sebagai landasan ijtihad. Artikel ini menemukan bahwa perceraian tidak boleh dilandaskan pada sebab pasangan menjadi difabel semata. Artinya, perceraian harus didasarkan pada unsur yang lebih substantif, yaitu broken marriage. Perkawinan yang rusak tidak selalu lahir dari sebab pasangan yang menjadi difabel. Banyak kasus menunjukkan bahwa meskipun pasangan masih normal, mereka abai terhadap kewajibannya dalam rumah tangga.